Cytokinins Act Directly on Lateral Root Founder Cells to Inhibit Root Initiation - Laplaze, Laurent (American Society of Plant Biologists, 2007)
In Arabidopsis thaliana, lateral roots are formed from root pericycle cells adjacent to the xylem poles. Lateral root development is regulated antagonistically by the plant hormones auxin and cytokinin. While a great deal is known about how auxin promotes lateral root development, the mechanism of cytokinin repression is still unclear. Elevating cytokinin levels was observed to disrupt lateral root initiation and the regular pattern of divisions that characterizes lateral root development in Arabidopsis. To identify the stage of lateral root development that is sensitive to cytokinins, we targeted the expression of the Agrobacterium tumefaciens cytokinin biosynthesis enzyme isopentenyltransferase to either xylem-pole pericycle cells or young lateral root primordia using GAL4-GFP enhancer trap lines. Transactivation experiments revealed that xylem-pole pericycle cells are sensitive to cytokinins, whereas young lateral root primordia are not. This effect is physiologically significant because transactivation of the Arabidopsis cytokinin degrading enzyme cytokinin oxidase 1 in lateral root founder cells results in increased lateral root formation. We observed that cytokinins perturb the expression of PIN genes in lateral root founder cells and prevent the formation of an auxin gradient that is required to pattern lateral root primordia.